Lagu Nusantara: Android Role Playing Game for Elementary School Music Learning - Nugraha, R. Gita Ardhy; Florentinus, Totok Sumaryanto; Utomo, Kamsidjo Budi (Journal of Primary Education, 2018)
The decreasing of student’s interest and motivation in Indonesian’s traditional music learning caused by less varied of the learning process and the lack of student’s knowledge about Indonesian’s traditional song. The lack of the utilization of gadget like educational games in the learning process also causes the decreasing of student’s interest and motivation. This study aims to verify the effectiveness of “Lagu Nusantara” games through student’s interest and motivation in the music art learning, especially about Indonesian’s traditional song. The method that used in this study is a quantitative method with the post-test only control group design for an experimental model which supported by the observation of games that used by students. The research subject was 89 elementary students who divided into a control group and experimental group (45 students for the control group and 44 students for experimental group). The result, “Lagu Nusantara” as the game is sufficient to promote student’s interest and motivation in the music art learning process, especially about Indonesian’s traditional song. As supporting data, this research obtained observation data for student’s interest and motivation which are well in the category (Interest score = 89.44%; motivation score = 87.78%).